2016
DOI: 10.3389/fnhum.2016.00326
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Emotional Content and Volume Level in Spoken Word Processing

Abstract: For visual stimuli of emotional content as pictures and written words, stimulus size has been shown to increase emotion effects in the early posterior negativity (EPN), a component of event-related potentials (ERPs) indexing attention allocation during visual sensory encoding. In the present study, we addressed the question whether this enhanced relevance of larger (visual) stimuli might generalize to the auditory domain and whether auditory emotion effects are modulated by volume. Therefore, subjects were lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
(108 reference statements)
3
6
0
Order By: Relevance
“…EPN studies have been commonly conducted with visual stimulation (Blechert et al 2012 ; Weinberg and Hajcak 2010 ) where EPN has been observed as a negative deflection over the occipito-parietal region, and its amplitude shows more pronounced deflection to emotional compared to neutral stimuli. In the current study, we observed more a central pattern of EPN possibly due to the use of auditory stimulation (Grass Bayer and Schacht 2016 ). Nevertheless, EPN exhibited emotion-sensitive characteristics.…”
Section: Discussionsupporting
confidence: 50%
“…EPN studies have been commonly conducted with visual stimulation (Blechert et al 2012 ; Weinberg and Hajcak 2010 ) where EPN has been observed as a negative deflection over the occipito-parietal region, and its amplitude shows more pronounced deflection to emotional compared to neutral stimuli. In the current study, we observed more a central pattern of EPN possibly due to the use of auditory stimulation (Grass Bayer and Schacht 2016 ). Nevertheless, EPN exhibited emotion-sensitive characteristics.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, in ERPs, preferential processing of descriptive and emotional words should be associated with modulations in early reflexive and later more elaborate ERP components. Because in our study the words were presented aurally, ERP modulations at frontocentral regions in the time range of the auditory P2 may be expected (Rohr & Abdel Rahman, 2015) instead of posterior EPN effects (but see Graß, Bayer, & Schacht, 2016, for the discussion of an "auditory EPN"). Later processing of emotional and descriptive stimuli as well as their interactions should arise in the LPP component, with increasing amplitudes as relevance increases.…”
Section: Introductionmentioning
confidence: 96%
“…They did not find that the modulation of these later components, linked to lexical-semantic processing, was affected by modulations of the physical characteristics of the auditory words (volume), which affected the N1-P2 complex. Grass et al (2016) argued that the auditory response evoked by the emotional content of words is thus distinct from early auditory evoked potentials. It is important to note that none of the above studies manipulated the prosodic contours of the auditory words, which were produced in a neutral manner.…”
Section: Introductionmentioning
confidence: 99%